Translation Analysis of Sexist Attitudes in Ronggeng Dukuh Paruk Novel - Maria Dita Manggarrani (MOZAIK HUMANIORA, 2019)
This research is a descriptive-qualitative research. It aims to determine the translation techniques used to convey the sexist attitudes to the target language and its impact for the translation quality in terms of accuracy, acceptability, and readability. The data of this research are 141 utterances that are obtained from both male and female characters. Those data were collected through content analysis and Focus Group Discussion. They were analyzed by using taxonomy, and componential analysis to see the cultural value. The result shows that there are 14 techniques which are applied in translating, those are; established equivalence, explicitation, modulation, pure borrowing, implicitation, paraphrase, generalitation, transposition, reduction, addition, discursive creation, particularization, compensation, and deletion. Furthermore, it reveals that the translation techniques determine the translation quality. Established equivalence results in the good quality of the translation. Meanwhile, the use of paraphrase produced a low quality translation in the target language. Moreover, the application of discursive creation results in non-sexist translation for two utterances.